Synthesis, Characterization and Optical Properties of a Bay- Functionalized Perylene Dye:N, N′-Didodecyl-1,7-di(3-methylphenoxy)- perylene-3,4:9,10-tetracarboxylic Acid Bisimide - Al-Khateeb, Basma Basil Ismael (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Perylene chromophore has an excellent aromatic conjugation and offers numerous advantages in many fields of application. One of their greatest advantages is the capability to functionalize the chromophore at its core/bay and imide positions with various substituents according to the desired application. In the present research on perylene dyes, we have synthesized a new core substituted perylene diimide in three consecutive steps focusing the application toward solar cells. Firstly, the starting raw material perylene dianhydride was brominated at 1,7- positions of the perylene chromophore to yield brominated dianhydride (Br–PDA). The product was imidized in the second step with a long dodecyl alkyl chain to yield brominated perylene diimide (Br-PDI). Finally, the targeted core substituted perylene diimide (PDI-m-Cresol) was synthesized upon bay substitution of perylene chromophore with m-cresol. The final compound is highly pure and characterized by FTIR, UV-vis and Emission measurements. For comparison, photophysics of the intermediate products were carried out in parallel. The absorption spectra of three perylene derivatives in nonpolar aprotic solvents and polar protic solvents show characteristic aromatic π–π* transition absorption peaks. In contrary, absorption in dipolar aprotic solvents shows irregular additional absorption bands (Br-PDA in NMP; Br-PDI in DMF; and PDI-m-Cresol in DMF and NMP) at higher wavelengths which were remained after microfiltering the solution. Interestingly, the emission spectra of the three perylene derivatives have shown traditional three characteristic emission peaks and were not influenced by additional weak absorption bands. Keywords: Perylene dyes, perylene derivatives, Bay-substitution, characterization of perylene derivatives.

ÖZ : Mükemmel bir aromatik konjugasyon yapısına sahip olan perilen boyar maddeleri pekçok uygulama alanında kullanılabilecek üstün özellikler sunmaktadırlar. En önemli üstünlüklerden biri gerek çekirdek/körfez gerekse imid pozisyonlarında çeşitli sübstitüentlerle perilen boyalarının fonksiyonelleştirilebilmesidir. Bu çalışmada, güneş hücreleri uygulamalarında kullanılmak amacıyle üç ardışık basamaklı reaksiyonlar ile körfez pozisyonunda fonksiyonleştirilen yeni bir perilen diimid sentezlenmiştir. İlk basamakta perilen anhidrit 1,7-pozisyonlarında bromlanmıştır (Br–PDA). İkinci basamakta dodesil sübsitientli ve bromlanmış diimid sentezlenmiştir (Br-PDI). En son basamakta ise perilen diimid körfez pozisyonunda m-kresol ile sübstitüe edilmiştir (PDI-m-Cresol). Saflandırılan ürünler FTIR, UV-Vis ve emisyon ölçümleri ile karakterize edilmiştir. Karşılaştırma için, ara ürünlerin fotofiziksel özellikleri de paralel biçimde incelenmiştir.Üç ayrı perilen türevinin apolar aprotik ve polar protik çözgenlerde ölçülen absorpsiyon spetrumlarında karakteristik π-π* geçiş absorpsiyon bandları gözlenmiştir. Buna karşın, dipolar aprotik çözgenlerde ölçülen absorpsiyon spektrumlarında mikro süzgeçten geçirildiğinde dahi yok olmayan düzensiz ve yeni bandlar gözlenmiştir (NMP'de Br-PDA; DMF'te Br-PDI; ve DMF ile NMP'de PDI-m-kresol).İlginç biçimde, üç ayrı perilen türevlerinin emisyon spektrumlarında düzensiz ve yeni absorbsiyon bandlarından etkilenmiyen karakteristik üç ayrı emisyon bandları yer almaktadır. Keywords: perylene diimid, körfez sübstitüe, fotonik, solar hücre.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2014. Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Dyes (Chemistry); Perylene Dyes; Photochemistry; Perylene dyes; perylene derivatives; Bay-substitution; characterization of perylene derivatives